The Digital Hereafter, or: Nirvana in the Cloud - Vanderbeke, Dirk (Journal of Posthumanism, 2024)
In the discussion of posthuman encounters, the focus is predominantly on robotics and the cyborg, artificial intelligence, and the implementation of technological elements into the human body. Less often explored is the complementary vision of the uploaded mind as a promise of life extension or even immortality. Nevertheless, there is, by now, quite a body of conceptual explorations, promises, warnings and also popularizations of this idea. The technological options described range from memory transfer to whole brain emulation or simulation, and they raise a multitude of theoretical, technological, philosophical and ethical concerns. Unsurprisingly, the assessment varies from enthusiastic celebration to dystopian nightmares, and the concepts have also been explored controversially in literary works. In my paper I outline the most important arguments and discuss some works of science fiction which explore visions of uploaded minds, most importantly Greg Evans’s Permutation City, Amitav Ghosh’s The Calcutta Chromosome, and Jeanette Winterson’s Frankissstein.